Effects of a design-based research approach on fourth-grade students' critical thinking, problem-solving skills, computational thinking, and creativity self-efficacy - Cavus, Emrah; Idil, Sahin; Donmez, Ismail (Springer, 2025)
This study examined the effectiveness of a design-based research approach in developing fourth grade students' critical thinking, problem solving, computational thinking, and creative self-efficacy skills. Although previous research has shown how design-based inquiry promotes higher-order thinking among middle and high school students. There is no comprehensive research supporting rural primary school students with this approach. Therefore, this study fills this gap by investigating design-based research (DBR) that can lead students to develop twenty-first century skills through primary science teaching. A quantitative pre-post-test design method was used to collect data over a 7-week period from 431 fourth grade students from two rural schools in T & uuml;rkiye. Findings showed that the design-thinking model was effective. The findings showed a significant improvement in critical thinking and creative self-efficacy. The effect on problem solving skills and computational thinking was negligible.
Keywords: Design thinking; Critical thinking; Problem-solving skills; Computational thinking; Creativity self-efficacy